A importância da obra missionária jesuítica em cultura e opulência do Brasil por suas drogas e minas - Alexandre, Luís Fernando Pessoa (2009)
This study analyzes the value of the Jesuit mission in Cultura e opulência do Brasil por suas drogas e minas (1982), by the Jesuit André João Antonil (1649-1716). The book, set in an important phase of the cultural formation of Brazil (between the end of the 17th and the beginning of the 18th centuries), explains all the details of the economic life of the colony by means of is main activities: sugar production, gold mining, tobacco cultivation and catle ranching. At that moment, the sugar production of northeastern Brazil was in a deep crisis, mainly by virtue of the competition with the Antillean sugar and the political instability in the Europe. Practically at the sarne time, the Portuguese colonists discover auriferous lodes in the region that corresponds nowadays to Minas Gerais state. As a consequence, the kingdorn of Portugal starts giving priority to the exploration of gold and diamonds in the Brazilian hinterland, activity which provokes a migration of people involved with the sugar and tobacco production to the mines. As result, a significant part of the enslaved manpower, the proprietors of devices and the capital used in agriculture goes to the gold mining. According to Antonil, this process of economical and population displacement in the Colony becomes harmful, because it contributes decisively to aggravate the crisis in agriculture, especially in the sugar production. Therefore the main aim of this study is to investigate the reasons why Antonil was against the way how the Portuguese and the inhabitants of the Colony lead the gold mining. As we will demonstrate, the author defends, even though implicitly, a social organization based on property, in opposition to the society characterizes by the dispersion and the lack of government. In this point, the member of the Company of Jesus discloses his concerns about the destination of the missionary work in the Colony. On account of this, his work are beyond the scope of the agricultural treaty, it's an instrument of evangelization.